Near-Net Shape Manufacturing of Miniature Spur Gears by Wire Spark Erosion Machining - Gupta, Kapil; Jain, Neelesh Kumar (Materials Forming, Machining and Tribology,, 2016)
This work describes an experimental investigation with the aim to evaluate and establish wire spark erosion machining (WSEM) as a viable alternative for high quality miniature gear manufacturing. External spur type miniature brass (ASTM 858) gears with 12 teeth, 9.8 mm outside diameter and 5 mm face width were manufactured by WSEM. The research work was accomplished in four distinct experimental stages viz., preliminary, pilot, main and confirmation. The aim, scope and findings of each stage are progressively presented and discussed. In essence, the investigation found that it was possible to manufacture miniature gears to high quality by using WSEM. Gears up to DIN 5 quality with a good surface finish (1.2 µm average roughness) and satisfactory surface integrity were achieved. The results suggest that WSEM should be considered a viable alternative to conventional miniature gear manufacturing techniques and that in some instances it may even be superior. This work will prove useful toresearchers and professionals in the field of miniature and micro-scale manufacturing and machining.